Treasury of Greek mythology : classic stories of gods, goddesses, heroes & monsters - Napoli, Donna Jo, 1948-; Balit, Christina (Washington, D.C. : National Geographic, 2011)
Presents illustrated retellings of classic Greek myths, sharing the stories of Zeus, Aphrodite, Apollo, Athena, Helen of Troy, Perseus, and Medusa, with sidebars for each god, goddess, hero, and monster that link the tales to constellations, history, geography, and culture, and including profiles, a family tree, and other resources.
School Library Journal starred, October 2011
Kirkus Starred, September 2011
Includes bibliographical references (p. 186-187) and index.
5.3
3-6
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Greek; Greek mythology